Fabrication and pool boiling performance assessment of microgroove array surfaces with secondary micro-structures for high power applications. (March 2022) - Tang, Heng; Xia, Liangfeng; Tang, Yong; Weng, Changxing; Hu, Zuohuan; Wu, Xiaoyu; Sun, Yalong
Abstract: Microstructure surface is an effective method to improve the boiling performance and has the feasibility of application in solving the heat dissipation problem of high-power electronics. This study develops microgroove array surfaces with secondary micro-structures (MSs) by two perpendicular electrical discharge machining processes to further maximize the boiling performance. Wavy electrodes composed of copper and tin foils with varying thickness and quantity are prepared to fabricate MSs with different structural parameters, and it is confirmed that the enhancement ratio of MSs on boiling performance increases with the increase of number and width of secondary microgrooves. The wall superheats at the onset of nucleate boiling of MSs are 45.3%–62.1% lower than that of smooth copper plate, and an outstanding critical heat flux of 2592.4 kW/m 2 with a maximum heat transfer coefficient of 138.6 kW/m 2 ∙ o C are achieved. The greatly enhanced boiling performance is attributed to the microgroove arrays and the secondary micro-structures, i.e., micro fins, ablation craters, and micropillars, which provide more nucleation sites and larger heat transfer area. Finally, the cell performance enhancement of concentrated photovoltaics using the nucleate boiling of MSs as thermal management solutions is evaluated as an example of its potential applications.